2017
DOI: 10.1002/jwmg.21232
|View full text |Cite
|
Sign up to set email alerts
|

Removal of an exotic fish influences amphibian breeding site selection

Abstract: For pond‐breeding species, the distribution of larvae is a reflection of habitat suitability and adult breeding site selection. Some species preferentially breed in ephemeral ponds, which can provide benefits for larvae. An alternative strategy used by adults to increase offspring survival is to detect aquatic predators and avoid them when selecting breeding sites. We investigated whether either of these types of breeding site selection are contributing to the negative correlation between the distributions of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 61 publications
1
16
0
Order By: Relevance
“…However, as discussed previously, emergent vegetation should not be allowed to completely cover wetlands, and the best management regime may be to create a mosaic of both sparsely and densely vegetated habitats (Fardell et al 2018). This outcome could also be achieved by pond draining to both eradicate Gambusia and thin macrophytes (Pollard et al 2017). One experimental study suggested that aquatic vegetation may provide insufficient refuge for aquatic invertebrates and amphibian larvae from Gambusia predation, and that direct removal of this fish is the best method to improve the conservation potential of restored wetlands (Shulse et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…However, as discussed previously, emergent vegetation should not be allowed to completely cover wetlands, and the best management regime may be to create a mosaic of both sparsely and densely vegetated habitats (Fardell et al 2018). This outcome could also be achieved by pond draining to both eradicate Gambusia and thin macrophytes (Pollard et al 2017). One experimental study suggested that aquatic vegetation may provide insufficient refuge for aquatic invertebrates and amphibian larvae from Gambusia predation, and that direct removal of this fish is the best method to improve the conservation potential of restored wetlands (Shulse et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The main threat to Green and Golden Bell Frog would be from the Plague Minnow ( Gambusia holbrooki ), which is a hardy species and can survive in puddles (Pollard et al . 2017). The only current feasible method for eliminating the Plague Minnow is by draining and drying wetlands and thus killing the fish or by natural drying (O'Meara & Darcovich 2015).…”
Section: Discussionmentioning
confidence: 99%
“…These adaptive management actions include removal of aquatic vegetation and draining of wetlands that have been colonised by the invasive Plague Minnow (Gambusia holbrooki, hereafter referred to as Gambusia) (O'Meara & Darcovich 2015;Pollard, et al 2017). Both these management actions have been undertaken in attempts to increase the breeding output of the Bell Frog, as some evidence suggests this species requires warm water temperatures and wetlands free from invasive fish to breed in (Pollard, et al 2017). High density and coverage of aquatic vegetation have been shown to reduce the water temperature and abundance of the Bell Frog (Lenga 2017), and hence has resulted in the prescription of emergent vegetation removal in managed populations.…”
Section: Introductionmentioning
confidence: 99%